I can't answer this because I don't know what she was starting with
Use this rule: <em>(x^a)^b = x^ab</em>
3(x + 2)^3/5 + 2 = 27
Subtract 3 from both sides
3(x + 2)^3/5 = 27 - 3
Simplify 27 - 3 to 24
3(x + 2)^3/5 = 24
Divide both sides by 3
(x + 2)^3/5 = 24/3
Simplify 24/3 to 8
(x + 2)^3/5 = 8
Take the cube root of both sides
x + 2 = 3/5√8
Invert and multiply
x + 2 = 8^5/3
Calculate
x + 2 = 2^5
Simplify 2^5 to 32
x + 2 = 32
Subtract 2 from both sides
x = 32 - 2
Simplify 32 - 3 to 30
<u>x = 30</u>
Answer:
y=-9x+35
Step-by-step explanation:
Answer:
6x^2+10x-6=0
Step-by-step explanation:
First, you need to add all like terms:
6x^2+8x-6=-2x
Now move the -2x to the other side:
6x^2+10x-6=0
Answer:
The present value of K is,
Step-by-step explanation:
Hi
First of all, we need to construct an equation system, so
![(1)K=\frac{169}{(1+i)} +\frac{169}{(1+i)^{2}}](https://tex.z-dn.net/?f=%281%29K%3D%5Cfrac%7B169%7D%7B%281%2Bi%29%7D%20%2B%5Cfrac%7B169%7D%7B%281%2Bi%29%5E%7B2%7D%7D)
![(2)K=\frac{225}{(1+i)^{2}} +\frac{225}{(1+i)^{4}}](https://tex.z-dn.net/?f=%282%29K%3D%5Cfrac%7B225%7D%7B%281%2Bi%29%5E%7B2%7D%7D%20%2B%5Cfrac%7B225%7D%7B%281%2Bi%29%5E%7B4%7D%7D)
Then we equalize both of them so we can find ![i](https://tex.z-dn.net/?f=i)
![(3)\frac{169}{(1+i)} +\frac{169}{(1+i)^{2}}=\frac{225}{(1+i)^{2}} +\frac{225}{(1+i)^{4}}](https://tex.z-dn.net/?f=%283%29%5Cfrac%7B169%7D%7B%281%2Bi%29%7D%20%2B%5Cfrac%7B169%7D%7B%281%2Bi%29%5E%7B2%7D%7D%3D%5Cfrac%7B225%7D%7B%281%2Bi%29%5E%7B2%7D%7D%20%2B%5Cfrac%7B225%7D%7B%281%2Bi%29%5E%7B4%7D%7D)
To solve it we can multiply
to obtain
, then we have
.
This leads to a third-grade polynomial
, after computing this expression, we find only one real root
.
Finally, we replace it in (1) or (2), let's do it in (1) ![K=\frac{169}{(1+0.2224)} +\frac{169}{(1+0.2224)^{2}}\\\\K=251.35](https://tex.z-dn.net/?f=K%3D%5Cfrac%7B169%7D%7B%281%2B0.2224%29%7D%20%2B%5Cfrac%7B169%7D%7B%281%2B0.2224%29%5E%7B2%7D%7D%5C%5C%5C%5CK%3D251.35)